Persepsi Guru Terhadap Program Pendidikan Inklusi Madrasah Ibtidaiyah : Studi Kualitatif di MIS Nurul Fadhillah - Rheina Sayla; Farras Fadhilah; M.Yasir Ardiansyah; Abdul Fattah Nasution (MERDEKA : Jurnal Ilmiah Multidisiplin, 2025)
This study is motivated by the need to understand teachers’ perceptions of the implementation of inclusive education in Indonesia, specifically at MIS Nurul Fadhillah. Inclusive education aims to provide equal learning opportunities for all children, including those with special needs, aligned with philosophical, legal, and pedagogical foundations. The purpose of this research is to explore teachers’ perceptions, attitudes, and the challenges they face in implementing inclusive education, as well as to identify strategies for enhancing the program’s success. The study employs a qualitative methodology with a case study approach, utilizing interviews and direct observations with teachers at the selected school. Data are collected systematically and analyzed thematically to provide a comprehensive understanding of perceptions and challenges encountered. The findings reveal that teachers’ perceptions significantly influence the success of inclusive education; positive attitudes and adequate competence enhance learning quality and inclusiveness. However, challenges such as insufficient training, limited facilities, and negative perceptions from society and parents remain.